Vienna-Heiligenstadt, Probusgasse 6 - Czoernig-Gobanz, Herta, 1886-1970 (artist)::::::::::::::: (2020)
Hand-colored etching of the inner courtyard of house no. 6 on the Probusgasse (Herrengasse 13 during Beethoven's time), with musical incipit for Beethoven's Sixth Symphony, estate signed. Beethoven lived in this house, where he wrote the Heiligenstadt Testament, from May-October 1802.